2015
DOI: 10.1002/ca.22590
|View full text |Cite
|
Sign up to set email alerts
|

Meniscal extrusion or subchondral damage characterize incident accelerated osteoarthritis: Data from the osteoarthritis initiative

Abstract: Introduction Knee osteoarthritis (KOA) is typically a slowly progressive disorder; however, a subset of knees progress with dramatic rapidity. We aimed to describe magnetic resonance imaging (MRI) findings that are associated with accelerated KOA. Materials and Methods We conducted a longitudinal descriptive study in the Osteoarthritis Initiative (OAI) cohort. We selected participants who had no radiographic KOA at baseline with one of the following in the most severe knee: 1) accelerated KOA (progressed to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

5
30
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
8

Relationship

7
1

Authors

Journals

citations
Cited by 33 publications
(35 citation statements)
references
References 20 publications
5
30
0
Order By: Relevance
“…While numerous studies have evaluated AKOA with data from the OAI [1,5,6,3,2,4,10,11] they have all focused on the first four years of the cohort. By studying people with AKOA after the 48-month visit of the OAI, we could explore which modifiable risk factors are consistently present and which risk factors are unique to the timing of incident AKOA.…”
Section: Discussionmentioning
confidence: 99%
“…While numerous studies have evaluated AKOA with data from the OAI [1,5,6,3,2,4,10,11] they have all focused on the first four years of the cohort. By studying people with AKOA after the 48-month visit of the OAI, we could explore which modifiable risk factors are consistently present and which risk factors are unique to the timing of incident AKOA.…”
Section: Discussionmentioning
confidence: 99%
“…Individuals with AKOA may initially be characterized by subtle changes related to knee pain that precede radiographic progression [7,8]. In preliminary analyses, we found that individuals with incident AKOA (n = 18) often have cartilage damage and meniscal pathology before any radiographic evidence of AKOA [8].…”
Section: Discussionmentioning
confidence: 99%
“…In preliminary analyses, we found that individuals with incident AKOA (n = 18) often have cartilage damage and meniscal pathology before any radiographic evidence of AKOA [8]. Within the OAI, magnetic resonance imaging revealed that individuals with no radiographic osteoarthritis (KL = 0) had a high prevalence of cartilage damage (76%), bone marrow lesions (61%), and meniscal pathology (>20%).…”
Section: Discussionmentioning
confidence: 99%
“…We recently characterized a group of individuals who develop an accelerated form of knee osteoarthritis, which we defined as a knee without radiographic osteoarthritis that develops incident advance‐stage disease in less than four years and often in just 12 months . Besides an accelerated rate of disease onset, individuals with accelerated knee osteoarthritis are more likely to be older, report greater knee pain, and experience a recent knee injury than their peers who develop a typical (gradual) onset of knee osteoarthritis.…”
mentioning
confidence: 99%